Seismic Performances of SRC Special-Shaped Columns and RC Beam Joints Under Double-Direction Low-Cyclic Reversed Loading - Zhang, Xiangyu; Xia, Qing; Ye, Bailong; Yan, Weiran; Deng, Zhiheng; Xiang, Ping (Frontiers in Materials, 2021)
Steel-reinforced concrete (SRC) special-shaped column and beam frame structure is a special structural form that can meet the requirements of high bearing capacity and satisfy the esthetic requirement of buildings. In this study, a new joint design approach is adopted to focus on the seismic behavior of SRC special-shaped column and reinforced concrete (RC) beam joints under low-cyclic double-directional reactions through pseudo-static tests with a controlled stirrup distance. The joints of SRC specimens were compared with those of RC specimens by controlling the area of steel and reinforcement, and hysteresis cycle skeleton curves and load and strain hysteresis cycles were analyzed. The specimen with profiled steel was found to have better energy dissipation capacity. The energy dissipation capacity and stiffness degradation of the nodes were analyzed. The test results showed that the energy dissipation capacity of the SRC joints was better than that of the conventional concrete column joints, and the stiffness degradation of RC joints was more significant than that of SRC joints.